Strategi Komunikasi dan Konseling Islam untuk Mencegah Pernikahan Dini - Armila, Armila; Dwi Nopryana, Rahmah (CV. Creative Tugu Pena, 2023)
Religious counselors play an important role in society. Islamic religious counselors act as mentors. According to Bloomfield in Gazali, Guide means to direct, guide or organize. In general, early marriage, namely marrying two people, one or both of whom are under 18 years of age, is still a serious problem in almost two-thirds of countries in the world (Yildirim et al., 2019). Although the practice of early marriage is legal, it is widely considered a violation of human rights and abuse, especially of adolescent girls. This research with the title